Colorimetric metal ion (II) Sensors Based on imine boronic esters functionalized with pyridine. (February 2021) - Sánchez-Portillo, Paola; Hernández-Sirio, Aime; Godoy-Alcántar, Carolina; Lacroix, Pascal G.; Agarwal, Vivechana; Santillán, Rosa; Barba, Victor
Abstract: The one-step synthesis of three imine boronic esters functionalized with pyridyl groups is described (1a -1c ). The presence or absence of a methyl group affects the whole conformation, being bent "L" or linear as determined by X-ray crystal diffraction. C–H⋯O, C–H⋯N, C–H⋯F and C–H … π hydrogen bond interactions support 2D supramolecular arrangements. Ligands were tested as metal ion (M 2+ ) sensors in solution. The addition of metal cations (Fe 2+, Co 2+ and Cu 2+ ) to 1a using methanol as solvent, showed significant color changes (purple, orange and green, respectively), while for metal cations Ni 2+, Zn 2+, Cd 2+ cations no color changes were observed. The sensitivity of compound 1a towards Fe 2+, Co 2+ and Cu 2+ was monitored by UV–Vis spectroscopy, where the presence of Fe 2+ produces new bands at 360 and 566 nm. For Co 2+ and Cu 2+ a remarkable intensity increase was observed at 290 nm band and new bands appear at 340 and 462 nm, respectively. The stoichiometry of the complexes 1a- Fe 2+, 1a -Co 2+ and 1a- Cu 2+ was determined by Job's plots being 1:3 (metal:ligand, complex [Fe (1a )3 ] 2+ ), in contrast with the stoichiometry 1:1 observed for 1b -Fe 2+ . In fact, the computed ΔG formation associated value showed a strong stabilization for the complex [Fe (1a )3 ] 2+ (−65.5 kcal/mol) in comparison with the possible complex [Fe (1b )3 ] 2+ (−29.7 kcal/mol). Detection limits are in the mM range (determined by UV–Vis) and μM range (determined by Fluorescence). An analogous bis-bidentate derivative (2a ) also shows similar behavior but stoichiometric interaction changes to 2:3 (metal:ligand) and detection limits are in the mM range obtained by UV–Vis and Fluorescence techniques. Graphical abstract: Imine-boronic esters were functionalized with pyridine giving place to the formation of 2D molecular structures at solid state which are supported by C–H⋯O, C–H⋯N, C–H⋯F and C–H … π hydrogen bonds. In methanol solution, the compounds showed visual color changes when are titrated with Fe 2+, Co 2+ and Cu 2+ ions. Thus, compounds can be used as colorimetric metal ion sensors, spectral changes by UV–Vis and Fluorescence also support this statement. Moderate values of LOD and LOQ were observed, given lower values for Cu 2+ even that those allowed in drinking water. Compounds are simple to use at real-time in naked-eye detection of Fe 2+ over Fe 3+ . Image 1 Highlights: Imine-boronic esters form 2D molecular structures in solid state supported by hydrogen bonds. Compounds showed visual color changes by titration with Fe 2+, Co 2+ and Cu 2+ in methanol solutions. LOD and LOQ were determinate by UV–vis and fluorescence. Compounds are simple to use at real-time as naked-eye detection of Fe 2+ over Fe 3+ .